1999
DOI: 10.1016/s0921-4534(99)00108-2
|View full text |Cite
|
Sign up to set email alerts
|

An unconventional Fermi liquid model for the optimally doped and overdoped cuprate superconductors

Abstract: Based on an unconventional Fermi liquid model, we present several results on the optimally doped and overdoped cuprate superconductors. For the normal state, we provide an analytic demonstration, backed by self-consistent Baym-Kadanoff (BK) numerical calculations, of the linear in T resistivity and linear in 1/ǫ optical conductivity, provided the interacting Fermi liquid has strong peaks in its density of states (van-Hove singularities in 2 dimensions) near the chemical potential µ. Moreover, we find that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…Our treatment shows that ω B here is nothing else but the fermionic energy w k−qo ,ǫ . The results here complement our earlier normal state results in 3,4 . ARPES experiments 10,11 have indicated that in the superconducting state, and, presumably, for ǫ → 0, the scattering rate is linear in T for k F close to the nodal directions, but otherwise saturates to a value which increases as k F approaches the vH points.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our treatment shows that ω B here is nothing else but the fermionic energy w k−qo ,ǫ . The results here complement our earlier normal state results in 3,4 . ARPES experiments 10,11 have indicated that in the superconducting state, and, presumably, for ǫ → 0, the scattering rate is linear in T for k F close to the nodal directions, but otherwise saturates to a value which increases as k F approaches the vH points.…”
supporting
confidence: 90%
“…The normal state result was obtained in 3,4 . Summarizing, within the Fermi liquid Eliashberg formalism, we calculate the one-particle scattering rate in the superconducting state of overdoped cuprates.…”
mentioning
confidence: 99%
“…From a theoretical point of view the linear-T dependence is not unexpected because already the bare two-loop diagram with unrenormalized couplings yields this behavior if the band filling is sufficiently close to the van Hove filling [20,21]. Hence it should be considered as an effect of the van Hove singularities and does not immediately imply a breakdown of the quasiparticle concept.…”
Section: Hole-doped Casementioning
confidence: 91%
“…The lower plots are for µ = 0.04t, which is further away from half-filling. The dashed lines in the left plots show the flow of Cooper couplings at the FS, the solid lines umklapp processes in the BZ diagonal VΛ(4,4,21), VΛ(3,4,21), and VΛ(5,4,21). The dashed-dotted lines denote Cooper processes between the saddle point regions with band energies below the FS (discussed in the text).…”
mentioning
confidence: 99%
“…[6,7]. On the other hand, there are various models to explain the strange normal state properties of unconventional superconductors, e.g., for cuprates on the basis of a van Hove scenario [8][9][10].…”
mentioning
confidence: 99%